Synthesis of the peptide Ac-Wahx-KTTKS and evaluation of the ability to induce in vitro collagen synthesis - Danila, A. S. Guglielmi [UNESP]; Ariane, M. Martinelli [UNESP]; Nathália, C. Rissi [UNESP]; Eduardo, M. Cilli [UNESP]; Christiane, P. Soares [UNESP]; Leila, A. Chiavacci [UNESP] (My University, 2016)
In this work, we report the synthesis of a peptide analogue of the KTTKS, termed Ac-Wahx-KTTKS and evaluate its cytotoxicity and role in biosynthesis of collagen for future application in skin aging. The peptide was obtained with purity higher than 97.5%. In the cytotoxicity assay, we observed non-toxic effects for Ac-WAhx-KTTKS at concentrations below 600 ôM for HaCaT and 500 ôM for HepG2 cells, respectively. After 24 and 48 h it was possible to observe significant changes in collagen synthesis in the groups treated with various concentrations of the peptide. In conclusion, the Ac-Wahx-KTTKS peptide increased collagen synthesis in fibroblasts by 80% and it is a promising candidate for improving skin aging.
Keywords: Ac-WAhx-KTTKS; Antiaging; Collagen biosynthesis; Cytotoxicity; Peptide synthesis; Skin functions.